Carboxyl-terminated hyperbranched magnetic silver-based catalyst as well as preparation method and application thereof
By coating SiO2 and γ-aminopropyltrimethoxysilane on magnetic Fe3O4 nanoparticles and blending them with end carboxylic hyperbranched polymers to form end carboxylic hyperbranched magnetic silicon shell particles and loading silver nanoparticles, the problem of easy oxidation and dissolution of existing magnetic silver-based catalysts is solved, and efficient catalysis and stable recycling are achieved.
Patent Information
- Application Number
- CN202411637383.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-04
AI Technical Summary
The existing magnetic silver-based catalysts are easily oxidized in air, and Fe3O4 nanoparticles dissolve in acidic media, which limits their application range and makes it difficult to achieve high catalytic efficiency and stability.
Magnetic Fe3O4 nanoparticles were prepared by co-precipitation method, and amino-aminopropyltrimethoxysilane was coated with SiO2 and γ-aminopropyltrimethoxysilane to form amino-amino-magnetic nanoparticles, and then blended with end carboxylic hyperbranched polymer to prepare end carboxylic hyperbranched magnetic silicon shell particles, and finally, silver nanoparticles were supported on their surface to form end carboxylic hyperbranched magnetic silver-based catalysts.
The catalyst has high catalytic efficiency and stability, can effectively catalyze the reduction of p-nitrophenol, and has good magnetic responsiveness, which facilitates the recovery and reuse of the catalyst. It can still maintain a 100% conversion rate after 14 cycle experiments.
Smart Images

Figure CN119549195A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, and in particular to a carboxyl-terminated hyperbranched magnetic silver-based catalyst and a preparation method and application thereof. Background Art
[0002] With the large-scale development of industrialization, the harm of p-nitrophenol to the environment is becoming increasingly serious. The catalytic reduction of p-nitrophenol to p-aminophenol has been widely studied. Commonly used metal catalysts are gold, palladium, platinum, silver, etc. Compared with other precious metals such as gold, palladium, and platinum, silver is not so expensive and has the same good chemical and physical properties. It can catalyze a variety of organic reactions and is currently a hot topic in research. Ag NPs are easily oxidized and agglomerated and lose their catalytic ability. They are also not easy to recycle and reuse. In order to solve these problems, the most effective way is to load silver onto a suitable magnetic carrier. Therefore, the preparation of loaded magnetic nano silver catalysts and their application in the treatment of organic pollutants in water bodies has important research value and scientific significance.
[0003] Fe3O4 magnetic particles can be easily and quickly separated from the solution by an external magnetic field, so using magnetic materials as carriers can effectively solve the problem of catalyst separation. Although loading silver into Fe3O4 magnetic particles can relatively improve the catalytic efficiency of silver, Fe3O4 nanoparticles are easily oxidized when exposed to air and will be dissolved by acidic media, which limits their application range.
[0004] Therefore, developing a magnetic noble metal catalyst with high catalytic efficiency is a problem that the present invention urgently needs to solve. Summary of the invention
[0005] In order to solve the problem of serious heavy metal ion pollution in the current environment, the present invention provides a carboxyl-terminated hyperbranched magnetic silver-based catalyst and a preparation method and application thereof. The hyperbranched magnetic silver-based catalyst is based on the unique tree-like structure in the hyperbranched polymer, and the surface of the loaded magnetic carrier increases the surface area to improve the loading amount and stability of its silver nanoparticles.
[0006] In order to achieve the above technical objectives, the present invention mainly adopts the following technical solutions:
[0007] In a first aspect, the present invention discloses a method for preparing a carboxyl-terminated hyperbranched magnetic silver-based catalyst, comprising the following steps:
[0008] Step 1, preparing magnetic Fe3O4 nanoparticles MNP by coprecipitation method;
[0009] Step 2, coating SiO2 and γ-aminopropyltrimethoxysilane on the surface of the magnetic Fe3O4 nanoparticles MNP in sequence to synthesize amino magnetic nanoparticles FSN;
[0010] Step 3, blending the amino-modified magnetic nanoparticles FSN with a carboxyl-terminated hyperbranched polymer solution for reaction, washing, separating the product with a magnet, and drying to obtain carboxyl-terminated hyperbranched magnetic silica shell particles FSNC;
[0011] Step 4: dissolving the carboxyl-terminated hyperbranched magnetic silica shell particles FSNC in a silver nitrate solution and stirring, then adding sodium borohydride to continue the reaction, washing, separating the product with a magnet, and drying to obtain the carboxyl-terminated hyperbranched magnetic silver-based catalyst Ag / FSNC.
[0012] In a preferred embodiment of the present invention, in step 1, the preparation method of magnetic Fe3O4 nanoparticles MNP includes: dispersing ferrous ions and ferric ions in a hydrochloric acid solution, stirring and heating evenly under a nitrogen atmosphere, and then slowly dripping a sodium hydroxide solution to adjust the pH to 10-12, continuing to keep the reaction warm, washing, separating the product with a magnet, and drying to obtain.
[0013] Preferably, the mass ratio of the ferrous ions, ferric ions, concentrated hydrochloric acid and sodium hydroxide is 1.12-1.13:1.08:0.36-0.38:15; the heating temperature is 70-100°C; the concentration of the concentrated hydrochloric acid solution is 36%-38%; and the concentration of the sodium hydroxide solution is 1.5-2.0 mol / L.
[0014] In a preferred embodiment of the present invention, in step 2, the preparation method of amino magnetic nanoparticles FSN includes: dissolving magnetic Fe3O4 nanoparticles MNP in a mixed liquid of anhydrous ethanol, concentrated ammonia water and deionized water, ultrasonically treating, adding ethyl orthosilicate thereto, adding γ-aminopropyltrimethoxysilane after a period of reaction to continue the reaction, washing, separating the product with a magnet, and drying to obtain the product.
[0015] Preferably, the mass percentage of concentrated ammonia water is 25-28wt%; after adding tetraethyl orthosilicate, the reaction is stirred at 25°C for 2 hours; after adding γ-aminopropyltrimethoxysilane, the reaction is stirred at room temperature for 4 hours; the mass volume ratio of the magnetic Fe3O4 nanoparticles MNP, tetraethyl orthosilicate, and γ-aminopropyltrimethoxysilane is 1:0.6:0.1 (g / mL / mL).
[0016] In a preferred embodiment of the present invention, in step 3, the preparation method of terminal carboxyl hyperbranched magnetic silica shell particles FSNC comprises: blending amino magnetic nanoparticles FSN with terminal carboxyl hyperbranched polymers dissolved in N,N-dimethylformamide and anhydrous ethanol, ultrasonically treating, heating and stirring the reaction under a nitrogen atmosphere, washing, separating the product with a magnet, and drying to obtain the product.
[0017] Preferably, the mass ratio of the terminal carboxyl hyperbranched polymer and the amino magnetic silica shell particles FSN is 3:1; the reaction is heated to 140°C under a nitrogen atmosphere for 12 hours; in step 4, the mass ratio of the terminal carboxyl hyperbranched magnetic silica shell particles FSNC, silver nitrate and sodium borohydride is 1:0.1:0.4; the reaction conditions of dissolving the terminal carboxyl hyperbranched magnetic silica shell particles FSNC in the silver nitrate solution are stirring at room temperature for 24 hours, and continuing the reaction for 2 hours after adding sodium borohydride.
[0018] In a preferred embodiment of the present invention, the carboxyl-terminated hyperbranched polymer is selected from the HyPer C10 series compounds of Wuhan Hyperbranched Resin Technology Co., Ltd., including any one of C100, C101, C102, C103, and C104; HyPer C20 series compounds, including any one of C201, C202, C203, and C204; HyPer C30 series compounds, including any one of C301, C302, C303, and C304; or HyPer C40 series compounds, including any one of C401, C402, C403, and C404; the molecular weight of the carboxyl-terminated hyperbranched polymer is 2000-8000 g / mol, and the acid value is 100-300 mgKOH / g.
[0019] In a second aspect, the present invention discloses a carboxyl-terminated hyperbranched magnetic silver-based catalyst prepared by the preparation method described in the first aspect.
[0020] In a third aspect, the present invention discloses a use of the carboxyl-terminated hyperbranched magnetic silver-based catalyst described in the second aspect in catalyzing the reduction of p-nitrophenol to p-aminophenol.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention provides a carboxyl-terminated hyperbranched magnetic silver-based catalyst that can effectively catalyze the reduction of p-nitrophenol (4-NP) to p-aminophenol (4-AP), and has good magnetic responsiveness, which is convenient for the recovery and reuse of the catalyst, and the catalytic experiment can be continued without treatment. Compared with traditional magnetic composite materials, the carboxyl-terminated hyperbranched magnetic silver-based catalyst was subjected to 14 cycles of experiments, and the conversion rate of 4-NP reached 100% within 80 minutes each time. The separation rate after each regeneration was between 90% and 95%, realizing the stable recycling of the catalyst. The carboxyl-terminated hyperbranched magnetic silver-based catalyst can be widely used in petrochemical, printing and dyeing, pesticide wastewater, etc., and has good development prospects.
[0023] 2. The carboxyl-terminated hyperbranched magnetic silver-based catalyst provided by the present invention has the characteristics of small product volume, wide application range, environmental protection, etc. The separation time is short, the requirements for separation equipment are low, and large-scale industrialization is possible. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The preparation route of amino-modified magnetic nanoparticles FSN; the black spheres represent magnetic Fe3O4 nanoparticles;
[0025] Figure 2 The preparation route of carboxyl-terminated hyperbranched magnetic silica shell particles FSNC;
[0026] Figure 3 XRD and FTIR images of the final product Ag / FSNC prepared in Example 1 and the final product Ag / FSN prepared in Example 2;
[0027] Figure 4 hysteresis loop diagrams of the Ag / FSNC prepared in Example 1 and the Ag / FSN prepared in Example 2;
[0028] Figure 5 The catalytic reaction constants and catalytic reusability diagrams of the Ag / FSNC prepared in Example 1 and the Ag / FSN prepared in Example 2. DETAILED DESCRIPTION
[0029] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0030] The catalyst Ag / FSN prepared by the present invention can significantly improve the stability of Fe3O4 by wrapping a SiO2 protective layer outside the magnetic Fe3O4 nanoparticles. Since the hyperbranched polymer has a unique tree-like structure, the polymer shell can prevent the aggregation of Fe3O4 particles and provide a large number of surface functional groups for further modification. The carboxyl-terminated hyperbranched polymer is wrapped on the surface of the magnetic nanoparticles with a silicon shell, and the magnetic polymer microspheres with a dendritic metal shell are designed to control the size and distribution of the metal particles, avoid the aggregation of the metal particles in the catalytic reaction, and thus improve the catalytic efficiency.
[0031] The technical solution of the present invention is further described in detail below in conjunction with specific implementation modes and drawings.
[0032] Example 1
[0033] The preparation of carboxyl-terminated hyperbranched magnetic silica shell silver-based catalyst (Ag / FSNC) comprises the following steps:
[0034] (1) Preparation of magnetic nanoparticles (MNPs)
[0035] A mixture of 4.0 g FeCl2·4H2O and 5.2 g FeCl3·6H2O was stirred in a solution of 40 mL deionized water and 0.85 mL concentrated HCl (36%-38%). Then, 250 mL of 1.5 mol / L NaOH solution was dripped into the mixture under vigorous stirring at 80°C N2 atmosphere. Dark black Fe3O4 nanoparticles were collected from the solution with a magnet. The particles were thoroughly washed with excess deionized water and anhydrous ethanol and dried under vacuum at 45°C.
[0036] (2) Preparation of amino magnetic nanoparticles (FSN)
[0037] Its preparation process is as follows Figure 1 As shown. 1.0g of Fe3O4 magnetic spheres were dispersed in 4ml of concentrated ammonia (25-28wt%) solution mixed with 50ml of deionized water and 80ml of anhydrous ethanol. After ultrasonic treatment for 10min, 0.6mL of tetraethyl orthosilicate (TEOS) with a concentration of more than 99% was added and stirred for 2h, and then 0.1mL of γ-aminopropyltrimethoxysilane (APTMS) with a concentration of 97% was injected into the resulting mixture with a micro syringe. After stirring for another 4h, the surface of the sample was modified by aminopropyl. The amino-functionalized material was collected with a magnet, washed three times with a mixture of ethanol and deionized water, and finally dried in vacuum at 45°C.
[0038] (3) Preparation of carboxyl-terminated hyperbranched magnetic silica shell particles (FSNC)
[0039] Its preparation process is as follows Figure 2 As shown. 1.0g Fe3O4 / SiO2-NH2(FSN) was dispersed in 165mL 18.2g / L terminal carboxyl hyperbranched polymer C100 in 150g ethanol DMF solution (absolute ethanol:DMF=1:4, where DMF concentration is greater than 99.5%) for amide reaction. The mixture was continuously stirred and refluxed at 140℃ N2 for 12h, then the nanocomposite material was magnetically separated, washed several times with DMF solution, and vacuum dried at 45℃ for 24h.
[0040] (4) Preparation of carboxyl-terminated hyperbranched magnetic silver-based catalyst (Ag / FSNC)
[0041] 1.0 g FSNC and 0.1 g AgNO3 were dispersed in 100 mL water, stirred at 25 °C for 24 h, 0.4 g NaBH4 was added and stirred for another 2 h, washed with water and ethanol three times in turn, collected by magnet, and dried under vacuum at 25-30 °C.
[0042] Comparative Example 1
[0043] The preparation of the catalyst comprises the following steps:
[0044] (1) Preparation of magnetic nanoparticles (MNPs)
[0045] A mixture of 4.0 g FeCl2·4H2O and 5.2 g FeCl3·6H2O was stirred in a solution of 40 mL deionized water and 0.85 mL concentrated HCl (36%-38%). Then, 250 mL of 1.5 mol / L NaOH solution was dripped into the mixture under vigorous stirring at 80°C N2 atmosphere. Dark black Fe3O4 nanoparticles were collected from the solution using a magnet. The particles were thoroughly washed with excess deionized water and anhydrous ethanol and dried under vacuum at 45°C.
[0046] (2) Preparation of amino magnetic nanoparticles (FSN)
[0047] 1.0g of Fe3O4 magnetic spheres were dispersed in 4ml of concentrated ammonia (25-28wt%) solution mixed with 50ml of deionized water and 80ml of anhydrous ethanol. After ultrasonic treatment for 10min, 0.6mL of tetraethyl orthosilicate (TEOS) with a concentration of more than 99% was added and stirred for 2h. Then, 0.1mL of γ-aminopropyltrimethoxysilane (APTMS) with a concentration of 97% was injected into the resulting mixture with a micro-syringe. After stirring for another 4h, the aminopropyl modified the sample surface. The amino-functionalized material was collected with a magnet, washed three times with a mixture of ethanol and deionized water, and finally dried under vacuum at 45°C.
[0048] (3) Preparation of amino-modified magnetic silver nanoparticles (Ag / FSN)
[0049] 1.0 g FSN and 0.1 g AgNO3 were dispersed in 100 mL water, stirred at 25 °C for 24 h, 0.4 g NaBH4 was added and stirred for another 2 h, washed with water and ethanol three times in turn, collected by magnet, and dried under vacuum at 25-30 °C.
[0050] Experimental Example 1 Structure and Performance Test of Carboxyl-Terminated Hyperbranched Magnetic Silver-Based Catalyst (Ag / FSNC)
[0051] Test samples: XRD and FTIR of the intermediate product MNP and the final product Ag / FSNC prepared in Example 1 and the final product Ag / FSN prepared in Comparative Example 1.
[0052] 1. XRD and FTIR analysis: The obvious diffraction peaks of Ag / FSNC and Ag / FSN at 2θ=30.076°, 35.057°, 43.053°, 56.935° and 62.52° are consistent with the positions of Fe3O4 reported in the literature. Four other diffraction peaks appeared at 2θ=38.1°, 44.3°, 66.4° and 77.5°, which were attributed to Ag (111), (200), (220) and (311) diffraction planes, respectively, which are consistent with the literature reports and JCPDS data card number 04-0783. Compared with Fe3O4, the FTIR graphs of Ag / FSNC and Ag / FSN at 1000cm -1 ~1100cm -1 The peaks of Si-O bond symmetric stretching vibration, 1570 cm -1 ~1600cm -1 The absorption peak of NH bending vibration appears. Figure 3 The former is at 1640cm -1 The peaks on the left and right are the positions of the C=O stretching vibration peaks in the amide, 1719 cm -1 The left and right are the peak positions of C=O stretching vibration in carboxylic acid. From the XRD and FTIR graphs, it can be seen that Ag / FSNC and Ag / FSN were successfully synthesized.
[0053] 2. Hysteresis loop (VSM) analysis: The vibrating sample magnetometer was used to test the magnetic properties of Ag / FSNC and Ag / FSN. The hysteresis curve (VSM) is shown in Figure 4 As shown. The MH curve represents that both catalysts are superparamagnetic materials without hysteresis. It can be seen that the saturation magnetization of Ag / FSN and Ag / FSNC is 43.3emu / g and 37.5emu / g. The saturation magnetization of MNP in the literature is 104.6emu / g. MNP has higher saturation magnetization than Ag / FSN and Ag / FSNC, indicating that the surface of Ag / FSNC is wrapped by the terminal carboxyl hyperbranched polymer, which affects the magnetization properties of Ag / FSNC and causes the magnetism to weaken.
[0054] Test Example 2 Catalytic Performance Test of Carboxyl-Terminated Hyperbranched Magnetic Silver-Based Catalyst (Ag / FSNC)
[0055] Test samples: Ag / FSNC prepared in Example 1 and Ag / FSN prepared in Comparative Example 1.
[0056] Take 10 mg of each of the Ag / FSNC prepared in Example 1 and the Ag / FSN prepared in Comparative Example 1 to catalyze 100 mL of 15 mg / L 4-NP and 50 mL of 4 g / L NaBH4. Under the condition of standing at 25°C, select a time interval of 1 to 15 min, measure the change in the conversion rate of 4-NP, fit the first-order kinetic equation, and obtain the reaction rate constant. After the catalytic reaction is completed, use a magnet to directly collect the sample in the conical flask, pour out the 4-AP and NaBH4 that are completely converted from 4-NP, and then add a newly configured mixture of 100 mL of 15 mg / L PNP and 50 mL of 4 g / L NaBH4 to the conical flask for the next experiment. With a cycle interval of 80 min, the catalyst was catalyzed continuously for 14 times, the concentration change of 4-NP was measured, the conversion rate of 4-NP was calculated, and a chart was drawn and the reaction rate constant (Kapp) of each cycle experiment was listed. The results are as follows Figure 5 As shown, it can be seen that the catalytic performance of the terminal carboxyl hyperbranched magnetic silica shell silver-based catalyst is better and the cyclic availability is stronger. With a cycle interval of 80 minutes, the conversion rate of 4-NP by Ag / FSNC can reach 100% after 14 consecutive catalysis. It is proved that the terminal carboxyl hyperbranched modified silver-based catalyst is helpful to improve the catalytic performance and repeated availability.
[0057] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a carboxyl-terminated hyperbranched magnetic silver-based catalyst, characterized in that: The steps include: Step 1, preparing magnetic Fe3O4 nanoparticles MNP by coprecipitation method; Step 2, coating SiO2 and γ-aminopropyltrimethoxysilane on the surface of the magnetic Fe3O4 nanoparticles MNP in sequence to synthesize amino magnetic nanoparticles FSN; Step 3, blending the amino-modified magnetic nanoparticles FSN with a carboxyl-terminated hyperbranched polymer solution for reaction, washing, separating the product with a magnet, and drying to obtain carboxyl-terminated hyperbranched magnetic silica shell particles FSNC; Step 4: dissolving the carboxyl-terminated hyperbranched magnetic silica shell particles FSNC in a silver nitrate solution for reaction, then adding sodium borohydride to continue the reaction, washing, separating the product with a magnet, and drying to obtain the carboxyl-terminated hyperbranched magnetic silver-based catalyst Ag / FSNC.
2. The method for preparing a carboxyl-terminated hyperbranched magnetic silver-based catalyst according to claim 1, wherein In step 1, the preparation method of magnetic Fe3O4 nanoparticles MNP includes: dispersing ferrous ions and ferric ions in a hydrochloric acid solution, stirring and heating evenly under a nitrogen atmosphere, and then slowly dripping a sodium hydroxide solution to adjust the pH to 10-12, continuing to keep the temperature and react, washing, separating the product with a magnet, and drying to obtain.
3. The method for preparing a carboxyl-terminated hyperbranched magnetic silver-based catalyst according to claim 2, wherein: The mass ratio of the ferrous ions, ferric ions, concentrated hydrochloric acid and sodium hydroxide is 1.12-1.13:1.08:0.36-0.38:15; the heating temperature is 70-100°C; the concentration of the concentrated hydrochloric acid solution is 36%-38%; and the concentration of the sodium hydroxide solution is 1.5-2.0 mol / L.
4. The method for preparing a carboxyl-terminated hyperbranched magnetic silver-based catalyst according to claim 1, wherein In step 2, the preparation method of aminated magnetic nanoparticles FSN includes: dissolving magnetic Fe3O4 nanoparticles MNP in a mixed liquid of anhydrous ethanol, concentrated ammonia water and deionized water, ultrasonically treating, adding ethyl orthosilicate thereto, adding γ-aminopropyltrimethoxysilane to continue the reaction after a period of reaction, washing, separating the product with a magnet, and drying to obtain the product.
5. The method for preparing a carboxyl-terminated hyperbranched magnetic silver-based catalyst according to claim 4, wherein: The mass percentage of the concentrated ammonia water is 25-28wt%; after adding tetraethyl orthosilicate, the reaction is stirred at 25°C for 2 hours; after adding γ-aminopropyltrimethoxysilane, the reaction is stirred at room temperature for 4 hours; the mass volume ratio of the magnetic Fe3O4 nanoparticles MNP, tetraethyl orthosilicate, and γ-aminopropyltrimethoxysilane is 1:0.6:0.1 (g / mL / mL).
6. The method for preparing a carboxyl-terminated hyperbranched magnetic silver-based catalyst according to claim 1, wherein In step 3, the preparation method of terminal carboxyl hyperbranched magnetic silica shell particles FSNC includes: blending amino magnetic nanoparticles FSN with terminal carboxyl hyperbranched polymers dissolved in N,N-dimethylformamide and anhydrous ethanol, ultrasonic treatment, heating and stirring the reaction under a nitrogen atmosphere, washing, separating the product with a magnet, and drying to obtain the product.
7. The method for preparing a carboxyl-terminated hyperbranched magnetic silver-based catalyst according to claim 6, wherein: The mass ratio of the terminal carboxyl hyperbranched polymer and the amino magnetic silica shell particles FSN is 3:1; the reaction is heated to 140°C under a nitrogen atmosphere for 12 hours; in step 4, the mass ratio of the terminal carboxyl hyperbranched magnetic silica shell particles FSNC, silver nitrate and sodium borohydride is 1:0.1:0.4; the reaction conditions of dissolving the terminal carboxyl hyperbranched magnetic silica shell particles FSNC in the silver nitrate solution are stirring at room temperature for 24 hours, and continuing the reaction for 2 hours after adding sodium borohydride.
8. The method for preparing a carboxyl-terminated hyperbranched magnetic silver-based catalyst according to any one of claims 1 to 7, wherein: The carboxyl-terminated hyperbranched polymer is selected from the HyPer C10 series compounds of Wuhan Hyperbranched Resin Technology Co., Ltd., including any one of C100, C101, C102, C103, and C104; the HyPer C20 series compounds include any one of C201, C202, C203, and C204; the HyPer C30 series compounds include any one of C301, C302, C303, and C304; or the HyPer C40 series compounds include any one of C401, C402, C403, and C404; the molecular weight of the carboxyl-terminated hyperbranched polymer is 2000-8000 g / mol, and the acid value is 100-300 mgKOH / g.
9. A carboxyl-terminated hyperbranched magnetic silver-based catalyst prepared by the preparation method according to claim 8.
10. Use of the carboxyl-terminated hyperbranched magnetic silver-based catalyst as claimed in claim 9 in catalyzing the reduction of p-nitrophenol to p-aminophenol.
Citation Information
Patent Citations
Preparation method of carboxyl functionalized hyperbranched magnetic mesoporous silica composite microspheres
CN103446964A
Preparation method of magnetic composite catalyst Ag / HNTs / Fe3O4
CN103638944A
Magnetic nanoparticles catalyst used for p-nitrophenol of catalysis hydrogenation and preparing method and application thereof
CN106311274A
Preparation method and application of Fe3O4-NH2@AgNPs composite material
CN108380247A